Ricerca educativa e razionalità pratica - Enza Colicchi (Firenze University Press, 2010)
Your search - any search - originates and begins with some problems that it seeks to solve. So the problem is the position that directs and guides the solution. The author focuses on those issues that bring us back to the Platonic and Aristotelian tradition, where "the problem" was already considered to be of critical reflection. The general problem in relation to which takes the form of educational research is that of rational control of the practices of education. Always relies on the teaching task to refer to the control of reason, the educational practice, to make rational educational interventions.